2019
DOI: 10.1007/s11357-019-00135-6
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid prolongs the lifespan of Drosophila melanogaster

Abstract: Wild-type CantonS flies of Drosophila melanogaster were treated with ellagic acid at 100 μM and 200 μM concentrations. Longevity assay showed male flies fed with 200 μM ellagic acid displayed longer mean lifespan and maximum lifespan than control flies. Female flies fed with 200 μM ellagic acid laid less number of eggs than control. The eclosion time was less in female flies fed with 200 μM ellagic acid. Ellagic acid fed female flies performed better than male flies and control flies for heat shock tolerance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
(73 reference statements)
3
6
0
Order By: Relevance
“…Using GC-MS analysis, we discovered that the ethanolic extract of TCE contains several compounds that have been shown to be antioxidants, including phytol 43 , beta-sitosterol, stigmasterol, campesterol 44 , and alpha-amyrin 45 . Concerning our results, several studies conducted in the Drosophila model also demonstrated that supplementation with dietary antioxidants was associated with the life span extension in fruit flies, such as green tea catechins and broccoli 46 , cocoa 47 , curcumin 48 , apple polyphenols 49 , lutein 50 , ellagic acid 51 , and xanthohumol 52 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using GC-MS analysis, we discovered that the ethanolic extract of TCE contains several compounds that have been shown to be antioxidants, including phytol 43 , beta-sitosterol, stigmasterol, campesterol 44 , and alpha-amyrin 45 . Concerning our results, several studies conducted in the Drosophila model also demonstrated that supplementation with dietary antioxidants was associated with the life span extension in fruit flies, such as green tea catechins and broccoli 46 , cocoa 47 , curcumin 48 , apple polyphenols 49 , lutein 50 , ellagic acid 51 , and xanthohumol 52 .…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the enhancement of adaptive response should ultimately prolong the life span. The findings from previous Drosophila research have shown that supplementation with phytochemical compounds could improve adaptive capacity in stressinduced aging, such as rutin 35,67 , ellagic acid 51 , naringenin 68 , and xanthohumol 52 . In this study, supplementation with TCE improved the recovery from cold and heat shocks in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ellagic acid, a component of strawberries, blackcurrants, pomegranates, walnuts and grapes, exhibited beneficial effects in a longevity assay on fruit flies. Interestingly, the mean and maximum lifespans of male flies were extended after consumption of 200 lM ellagic acid, whereas female flies laid less eggs in response to ellagic acid (Kharat et al 2020). However, other studies observed prolonged lifespans in female flies compared with their male counterparts (Staats and L€ uersen et al 2018).…”
Section: Toxicity Trials In Drosophila Melanogastermentioning
confidence: 99%
“…Ellagic acid can be obtained through SmF of orange peel waste with Aspergillus fumigatus [34]. When female Drosophila melanogaster were fed with a diet containing ellagic acid (200 µM) there was a decrease in oviposition [35]. The SSF of lemon, orange, grapefruit, and tangerine waste carried out with Fusarium oxysporum, Penicillium purpurogenu, Trichoderma harzianum, and Aspergillus niger, produced chlorogenic acid, didymin, apigenin 7-O-apiosyl-glucoside, pinoresinol, medioresinol, naringin, and hesperidin [36].…”
Section: Fermentation Of Plant-based Materials As Source Of Biopestic...mentioning
confidence: 99%